A REVIEW FOR A VORTEX TUBE PERFORMANCE (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
This research provides a comprehensive review of previous studies on the performance of vortex tubes, offering detailed information derived from both experimental, theoretical, and experimental and theoretical investigations. Vortex tubes are classified into two main types: counterflow and parallel flow, to facilitate the reader’s understanding of their operating mechanisms. Performance parameters of vortex tubes are extensively presented, based on the available experimental and theoretical results to date. These include the maximum recorded values for performance coefficient, temperature differences at both hot and cold outlets, as well as the overall cooling efficiency of the device, thus providing a clear and simplified reference for researchers interested in this field. It has been observed that the influence of multiple nozzle manifolds and their inclination angles has not been sufficiently investigated. Therefore, it is recommended that future research be directed towards studying the impact of these factors on improving the performance of vortex tubes more accurately and comprehensively. The objective of this study is to collect and analyze previous research on vortex tubes and to classify the studies into three main categories: experimental, numerical, and combined experimental-numerical. This classification aims to facilitate researchers' review of existing literature and support the development of future research.